The Cost of Health Care Services in Urban and Intercity Road Traffic Accidents - Alireza AMANOLLAHI; Mohammad HOSEINI KASNAVIEH; Nader TAVAKOLI; Mohammad VEYSI; Ali TAHMASEBI (Tehran University of Medical Sciences, 2019)
The Cost of Health Care Services in Urban and Intercity Road Traffic Accidents